Making room in engineering design practices. Issue 2 (3rd May 2016) - Petersen, Rikke Premer; Buch, Anders
ABSTRACT: This article aims to explore the challenges that occur from a practice perspective when a new approach to engineering design enters an existing ecology of professional practices in a workplace. Using four empirical episodes, the article illustrates a concrete effort to challenge what counts as 'real engineering' or what is recognized as part of the engineering expertise. Using an ethnographic, case-study-based research design the article documents how holistically minded professionals do engineering design 'by other means', in ways that strive to promote user experience approaches. The article aims to show how engineering practices do not exist in isolation within an organization and how ambitions to transform professional engineering work practices require a change in the very ecologies of practices that exist across an organization.